2021
DOI: 10.3389/fimmu.2021.646650
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Renal Macrophage, AIM, and TGF-β1 Expression in Renal Fibrosis Progression in IgAN Patients

Abstract: ObjectiveTo analyze the expression of macrophages, AIM, TGF-β1 in the kidney of IgAN patients, and to explore the role of macrophages, AIM, TGF-β1 in the progression of renal fibrosis in IgAN patients.MethodsThe paraffin specimens of renal tissue from 40 IgAN patients were selected as the observation group. At the same time, paraffin specimens of normal renal tissue from 11 patients treated by nephrectomy were selected as the normal control group. We observed the distribution of macrophages, the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Moreover, gene ontology functional enrichment among the 640 genes revealed that they were mainly enriched in terms of “transforming growth factor beta”, “apoptotic process”, “NF-kappa B signaling” and “toll-like receptor signaling pathway”, “kinase regulator activity” and “cell adhesion” (Fig. 8G ), which were previously demonstrated to related to renal fibrosis or ECM deposition [ 20 22 ]. KYOTO ENCYCLOPEDIA OF GENES AND GENOMES pathway enrichment among these genes showed that they were mainly enriched in terms of “TNF signaling pathway”, “Hepatitis” and “virus infection” (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, gene ontology functional enrichment among the 640 genes revealed that they were mainly enriched in terms of “transforming growth factor beta”, “apoptotic process”, “NF-kappa B signaling” and “toll-like receptor signaling pathway”, “kinase regulator activity” and “cell adhesion” (Fig. 8G ), which were previously demonstrated to related to renal fibrosis or ECM deposition [ 20 22 ]. KYOTO ENCYCLOPEDIA OF GENES AND GENOMES pathway enrichment among these genes showed that they were mainly enriched in terms of “TNF signaling pathway”, “Hepatitis” and “virus infection” (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…In the process of EMT, epithelial cells adapt to the stimulation of the immune microenvironment, thereby changing the plasticity phenotype. Macrophages in the immune microenvironment are considered to be the main part of driving kidney inflammation and fibrosis, because they synthesize and secrete a variety of molecules that promote or participate in the process of kidney fibrosis, such as growth factors, enzymes, and matrix proteins [ 37 , 38 ]. Among them, TGF- β secreted by macrophages is considered to be one of the main factors that promote fibrosis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD163 + macrophages are considered to be M2c macrophages with anti-inflammatory and pro-fibrotic functions ( 10 ). Indeed, previous studies on IgAN showed that CD163 + macrophage subsets correlated with degree of interstitial fibrosis ( 21 ), and that CD163 + macrophages play a more important role in progression of IgAN fibrosis than other kinds of macrophages ( 8 ). Relatedly, we demonstrated that u-sCD163 levels were higher in patients with severe tubule-interstitial lesions, while being significantly correlated with global glomerulosclerosis and segmental glomerulosclerosis score.…”
Section: Discussionmentioning
confidence: 99%
“…Wound-healing macrophages (M2a), M2b and regulatory macrophages (M2c) ( 7 ). Macrophages infiltration in IgAN kidneys are predominantly composed of CD163 + M2c macrophages ( 8 ).…”
Section: Introductionmentioning
confidence: 99%